An optimization approach for long term investments planning in energy - Montagna, Jorge Marcelo (2014)
This paper presents a mathematical programming model for planning investment in energy sources. The problem formulation considers the use of renewable and not renewable sources and demands, revenues, operation, start-up, and amortization costs of new energy facilities and the amount of reserves of fossil fuels. The objective is the maximization of the Net Present Value (NPV) in the time horizon. The results provide the visualization of the investments made: time periods in and their amounts and also how the energy matrix is affected by those investments. In particular the model was applied to Argentina. The most important feature of the model is the ability to assess and to plan the evolution of the energetic matrix at different circumstances.